Time and depth variability of radon concentration and its relationship with other physicochemical parameters in an artificial lake subject to strong anthropogenic control - Luís, Gustavo P.S.; Pereira, Alcides J.S.C.; Sêco, Sérgio L.R.; Filho, José Augusto; Neves, Luís (The Science of the total environment, 2025)
Understanding the interaction between groundwater and surface water is crucial for an effective water management. This study investigates the vertical variability of radon gas (Rn-222) concentrations and other physicochemical parameters (pH, electrical conductivity, redox potential, and temperature) in an artificial lake (Aguieira Dam's reservoir) in the Mondego River, Portugal, that is intensively controlled by human factors. Over nine surveys conducted from May 2022 to September 2023, we observed significant vertical and temporal variations in these parameters, revealing complex patterns of water column stratification driven primarily by thermal dynamics and dam management practices. The study found that during periods of complete thermal stratification, Rn-222 concentrations were higher at mid-thermocline and at the riverbed, indicating traces of potential groundwater inputs, while at the epilimnion showed lower concentrations due to atmospheric exhalation. Conversely, during not complete stratification conditions, typically observed during higher water turbulence or lower water levels, the water column exhibited more homogeneous physicochemical profiles. Nevertheless, in some cases that could be related to increased precipitation prior to the sampling, it was observed also traces of groundwater input, highlighted by the radon tracer and confirmed by other physicochemical parameters. This study highlights the complex dynamics of water column stratification in artificial lakes whose inputs and outputs are heavily controlled by humans. The dam management itself is responsible for the complete inversion of the natural cycle of water level expected in a natural environment, thus these findings underscore the importance of considering both natural and anthropogenic factors in the management of water resources, particularly in dam-influenced systems, where vertical stratification and groundwater-surface water interactions can significantly impact water quality and the overall ecosystem health. This work contributes to a better understanding of the hydrological processes in dam-regulated river systems, providing insights for water resource management. [Display omitted] •Study of an artificial lake strongly affected by the anthropogenic management of the water inputs and outputs;•The vertical variability of radon gas, as also of the pH, electrical conductivity, redox potential and temperature;•Establishment of an internal structure in the water column according to the temperature profile with correspondence to the radon gas patterns;•Temporal variation of water column - the dry, wet and transient seasons and its relationship with the radon gas.